2016
DOI: 10.1038/srep34143
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in pH destabilizes individual vault nanocages by weakening the inter-protein lateral interaction

Abstract: Vault particles are naturally occurring proteinaceous cages with promising application as molecular containers. The use of vaults as functional transporters requires a profound understanding of their structural stability to guarantee the protection and controlled payload delivery. Previous results performed with bulk techniques or at non-physiological conditions have suggested pH as a parameter to control vault dynamics. Here we use Atomic Force Microscopy (AFM) to monitor the structural evolution of individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 36 publications
1
20
0
Order By: Relevance
“…Mechanical studies of protein shells are not limited to viruses containing the native genomic content 136 . For example, experiments have been performed on cowpea chlorotic mottle virus loaded with phthalocyanine dyes 137 , bacterial nanocompartment encapsulins and Aquifex aeolicus lumazine synthase 138,139 , eukaryotic vaults 140 and artificial designer protein shells such as octahedral O3-33 cages 138 . Virus-cell interactions can also be characterized by AFM, and the initial binding of both influenza and rabies viruses to eukaryotic cells has been shown to be multivalent 141,142 .…”
Section: Case Studiesmentioning
confidence: 99%
“…Mechanical studies of protein shells are not limited to viruses containing the native genomic content 136 . For example, experiments have been performed on cowpea chlorotic mottle virus loaded with phthalocyanine dyes 137 , bacterial nanocompartment encapsulins and Aquifex aeolicus lumazine synthase 138,139 , eukaryotic vaults 140 and artificial designer protein shells such as octahedral O3-33 cages 138 . Virus-cell interactions can also be characterized by AFM, and the initial binding of both influenza and rabies viruses to eukaryotic cells has been shown to be multivalent 141,142 .…”
Section: Case Studiesmentioning
confidence: 99%
“…Although it is well known that they participate in these functions, the mechanism through which it intervenes is not defined. Vault structure is highly conserved among different eukaryotic organisms [20,25,33], which indicates the importance of its functions and the putative biocompatibility that it can present as nano-DDSs [33].…”
Section: Eukaryotic Vaultsmentioning
confidence: 99%
“…Under physiological conditions there is a balance between the closed and open conformations (separate halves) of vaults, allowing the entry of molecules [39]. An acidification of the medium destabilizes the bonds between monomers, with the exception of the strong hydrophobic joints between the head-helix domains, giving rise to a “flower-like” structure [20,40]. Low-pH condition triggers vault conformational change.…”
Section: Eukaryotic Vaultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another experiment showed that decreasing the pH weakened the bonds between proteins. It was proposed that the observed responses of the vaults at low pH values were due to the strong polar characteristic of the lateral interaction between adjacent proteins 256 . It also has been shown that the vault maintained its structure at pH values ranging from 6.0 to 7.5, but the particle was reported to be 15% shorter in length at pH 6.0 compared to its length at pH 7.5.…”
Section: - Ncs As Platforms For Ddssmentioning
confidence: 99%